2019
DOI: 10.1073/pnas.1901824116
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity and interindividual variability in the response of the human circadian system to evening light

Abstract: Before the invention of electric lighting, humans were primarily exposed to intense (>300 lux) or dim (<30 lux) environmental light—stimuli at extreme ends of the circadian system’s dose–response curve to light. Today, humans spend hours per day exposed to intermediate light intensities (30–300 lux), particularly in the evening. Interindividual differences in sensitivity to evening light in this intensity range could therefore represent a source of vulnerability to circadian disruption by modern lighting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
291
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(323 citation statements)
references
References 49 publications
17
291
2
Order By: Relevance
“…These findings will help to improve interpretation of assessments using this sensor, which is critical in research studies with a circadian component. The human circadian system responds non-linearly to light intensity, with high sensitivity to light levels below 100 lux [2,3,19]. Consequently, it is important for devices used in sleep and circadian studies to accurately capture light intensities at these levels, which are typically experienced in everyday life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings will help to improve interpretation of assessments using this sensor, which is critical in research studies with a circadian component. The human circadian system responds non-linearly to light intensity, with high sensitivity to light levels below 100 lux [2,3,19]. Consequently, it is important for devices used in sleep and circadian studies to accurately capture light intensities at these levels, which are typically experienced in everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Light is the key zeitgeber (time cue) responsible for synchronizing the circadian clock [1] and is therefore a critical measure in studies assessing circadian outcomes. The human circadian system is highly sensitive to light, with its dynamic range overlapping with typical indoor light levels [2,3], and peak sensitivity to blue light [4,5]. Accurate assessment of an individual's light exposure profile, including under typical indoor lighting, is therefore essential to understanding the impact of light on the circadian system.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3B and D show the situation in which the transition occurs in the opposite direction (from antialigned to aligned). Phillips et al (2019) recently showed that there are interindividual differences in light sensitivity between subjects, which may affect sleep and circadian timing. These interindividual differences in light sensitivity may also be the reason that not all animals will arrive in the split state when subjected to constant light or a forced desynchrony protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Other circadian mechanisms exhibit similar variation. As a recent example, melatonin suppression due to light exposure was found to vary significantly between subjects (18).…”
Section: A Personalized Phase Response Curve Of Crhrmentioning
confidence: 99%